System dynamics : modeling and simulation of mechatronic systems - Karnopp, Dean.; Margolis, Donald L.; Rosenberg, Ronald C.; Wiley InterScience (Online service) (Hoboken : Wiley, 2012)
An expanded new edition of the bestselling system dynamics book using the bond graph approach A major revision of the go-to resource for engineers facing the increasingly complex job of dynamic systems design, System Dynamics, Fifth Edition adds a completely new section on the control of mechatronic systems, while revising and clarifying material on modeling and computer simulation for a wide variety of physical systems. This new edition continues to offer comprehensive, up-to-date coverage of bond graphs, using these important design tools to help readers better understand the various compone.
Frontmatter -- Introduction -- Multiport Systems and Bond Graphs -- Basic Bond Graph Elements -- System Models -- State-Space Equations and Automated Simulation -- Analysis and Control of Linear Systems -- Multiport Fields and Junction Structures -- Transducers, Amplifiers, and Instruments -- Mechanical Systems with Nonlinear Geometry -- Distributed-Parameter Systems -- Magnetic Circuits and Devices -- Thermofluid Systems -- Nonlinear System Simulation -- Appendix: Typical Material Property Values Useful in Modeling Mechanical, Acoustic, and Hydraulic Elements -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Systems engineering; System analysis; Bond graphs; Mechatronics; Bond graphs; Mechatronics; System analysis; Systems engineering; Electronic books